Case report: reuse of tirofiban leads to very severe thrombocytopenia - Li, Yuqing; Qiu, Jiuchun; Gao, Yi; Li, Guangping (Frontiers in Cardiovascular Medicine, 2023)
Telofiban is a class of small molecule non-peptide tyrosine derivatives containing RGD sequences. It is the only platelet surface glycoprotein (GP) IIb/IIIa receptor antagonist (GPI) currently marketed in China. In patients with ST-segment elevation myocardial infarction(STEMI) who receive the percutaneous coronary intervention (PCI) with a heavy thrombotic load, postoperative intravenous tirofiban can prevent complications of myocardial ischemia due to sudden coronary artery occlusion. With the increase in the clinical use of tirofiban, the number of adverse reactions related to thrombocytopenia induced by tirofiban has gradually increased. Still, most of them have thrombocytopenia after the first use. We report one case of very severe thrombocytopenia following the reuse of tirofiban. A 65-year-old male patient underwent PCI, implanted three stents five days before admission, and was anticoagulated with tirofiban antiplatelet and nadroparin calcium anticoagulation after surgery, and no thrombocytopenia was found. The patient with a history of hypertension, type 2 diabetes, diabetic nephropathy, cerebral infarction, and coronary artery stenting usually took aspirin 100mg of and clopidogrel 75mg of antiplatelet therapy. The patient still retains 80% stenosis due to anterior descending branches, and it is planned to undergo PCI again half a month later. One day after discharge, the patient suddenly felt chest tightness and wheezing. The laboratory showed hypersensitivity troponin 2.85ng/ml (normal 0-0.0268ng/ml), and the admission ECG showed ST-T changes in leads I, aVL, V5-V6. On the 6th day of hospitalization, PCI was performed, a stent was implanted in the proximal section of the anterior descending branch opening, and tirofiban antiplatelet therapy was given after surgery. About 10 minutes after the tirofiban infusion, the patient suddenly shivered, accompanied by convulsions, accompanied by elevated body temperature (up to 39.4°C), accompanied by epistaxis and microscopic hematuria. An urgent blood test showed that the platelets dropped to 1×109/L, tirofiban and aspirin stopped immediately, and the antiplatelet therapy of clopidogrel was retained. After infusion of methylprednisolone sodium succinate and gamma globulin, the patient's platelets gradually recovered, and the patient was successfully discharged seven days later in stable condition.